Homeschooling Parents’ Demotivation And Remotivation Processes: A Pilot Study in Hungary - Mikusová, Melinda (Working Papers in Language Pedagogy, 2020)
Homeschooling, especially in a country like Hungary, where it is a legalized but not a recognized form of education, is not easy. This small-scale pilot study set out to examine the motivational dynamics of four Hungarian homeschooling parents by looking at processes of demotivation and remotivation. An interview guide was used to elicit answers from the participants. It was composed of three sections: questions on background information, questions on demotivation, and questions on remotivation. The results revealed that the participants became most demotivated mainly due to external, milieu-related influences, such as the lack of community awareness, outside pressure, negative public opinion, and facing constant criticism. In terms of remotivating attributes, the internal forces, such as some unexpected “magic” moments, satisfaction with the results, and experiences of success and enjoyment, appeared to be more influential. The results offer new insight into motivation research, as demotivation and remotivation are still relatively under-researched, and provide some basic information about the state of Hungarian homeschooling education.